(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
The article explores the opportunities for utilizing regenerated fibers in the production of non-woven materials and spinning. One of the means for efficient and economical use of the raw material base in the spinning and weaving industry is the rational recycling of production waste. At this stage of the research, the proposed new fiber opening equipment was used to process waste yarns without prior cutting on a cutting machine. Analysis of the properties of the obtained fibers confirmed the possibility of obtaining fibers suitable for textile product manufacturing. To investigate the spinnability of the regenerated fibers, the spinnability limit and the minimal possible linear density of the yarn were determined, which can be in the range of 25-29 tex.